Holocene organic geochemical record from the Western Indus continental shelf (northern Arabian Sea). (June 2020) - Kahkashan, Sanober; Chen, Jianfang; Wang, Xinhong; Clift, Peter D; Jalali, Bassem; Inam, Asif; Saleem, Monawwar; Aftab, Javed; Ji, Zhongqiang; Bai, Youcheng; Li, Zhongqiao; Haiyan, Jin; et al.
Primary production on the Western Indus continental shelf has been linked to the large quantities of nutrients delivered to the shelf by the Indus River. Multiple geochemical tracers and biomarker records, including stable isotopes (δ 13 C and δ 15 N), total organic carbon (TOC), total nitrogen (TN), molar carbon/nitrogen (C/N) ratio, the branched and isoprenoid tetraether (BIT) index, and glycerol dialkyl glycerol tetraether (GDGT), have been analyzed from the Indus-23AP sediment core recovered from the northern Arabian Sea. Our records show evidence of a mixture of marine and terrestrially derived organic matter (OM) during the last 14, 000 years, as indicated by the C/N ratio, δ 13 C, δ 15 N, and the BIT index. The three sterol biomarkers (brassicasterol, dinosterol, and cholesterol) show concurrent enrichments during the last 3 millennia reflecting increased phytoplankton abundance because of increased Indus river discharge of nutrients during the summer monsoon. GDGT crenarchaeol enrichment is related to the BIT index. The TEX86 -derived sea surface temperature (SST) record is shifted toward the summer season because Crenarchaeota are more abundant and active during periods of high primary production. SSTs indicate a long-term warming trend during the Holocene related to increasing winter insolation in the low latitudes northern Hemisphere.